Optimizing Digital Marketing Strategies for MSME: A Case Study of Nostalgia Coffee - Lady; Meilani, Lara; Cuandra, Fendy (Universitas Muhammadiyah Palembang, 2025)
The current trend in digital marketing presents a significant opportunity, particularly for Micro, Small, and Medium Enterprises (MSMEs) in the Industry 4.0 era. Digital marketing offers many advantages over traditional methods, especially its ability to track and measure strategic effectiveness. This research aims to optimize digital marketing strategies to enhance promotion and sales performance for the MSME Nostalgia Coffee. A qualitative approach was used, employing method triangulation through interviews, observation, and content analysis to validate findings and ensure data credibility. Results show that optimizing digital marketing—especially through Instagram, WhatsApp Business, and online food delivery platforms—led to a measurable impact. Instagram account reach increased by 26.3%, with a 69.2% rise in followers over 14 days. Customer interaction also improved, with 34 engaged accounts, comprising 86.3% followers and 13.7% non-followers. Furthermore, Google Reviews improved with 14 new reviews, increasing total online ratings and strengthening public perception. These findings suggest that strategic implementation of digital tools can enhance customer engagement and brand visibility. Future studies are recommended to apply these strategies on a wider scale and over a longer timeframe to achieve sustained growth and adaptability.